Counteracting the effects of paraquat on photosynthesis by chlorogenic acid - Laskay, Gábor; Lakos, Ádám (Acta Biologica Szegediensis, 2011)
The effects of chlorogenic acid on the actions of paraquat on photosynthesis were studied in green pepper (Capsicum annuum) leaves under medium- and low-irradiance conditions by following various characteristic parameters of chlorophyll fluorescence (e.g. fast fluorescence induction kinetics and light intensity-dependence of non-photochemical quenching (NPQ)). Simultaneous treatment with 1 mM chlorogenic acid for 30 minutes eliminated the light intensity-dependent elevation of the non-photochemical quenching (NPQ) induced by 1 mM paraquat, and it also counteracted the paraquat-induced decrease in variable fluorescence (Fv/Fm). These protective actions were seen both under medium- and low-irradiance conditions. Importantly, there was no need for pretreatment of the leaves with chlorogenic acid. These results indicate that chlorogenic acid is capable of protecting green plant cells from the actions of paraquat.